2013
DOI: 10.4236/mc.2013.22003
|View full text |Cite
|
Sign up to set email alerts
|

Extending the interval for port-a-cath maintenance

Abstract: Objective: The objective of this study is to assess the outcome of port-a-cath (PAC) maintenance every three months in patients with gynecologic malignancies with the goal of standardizing a safe and appropriate interval that would maintain patency and minimize side effects. Methods: We performed a retrospective medical record review and evaluation of all patients with a Bard © PAC who were noted to have no evidence of disease (NED) during the years 2003 to 2010. The interval between accessions and any complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Some studies have suggested extending flush interval to 2 months, 9,19 and others have suggested prolonging flush interval to 3 months or longer. 10,25,26 Clari et al 27 reported very lowquality evidence of no statistically significant difference in occlusion rates between short and long flush interval. However, they did not conclude whether flush interval could be extended to a specific time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested extending flush interval to 2 months, 9,19 and others have suggested prolonging flush interval to 3 months or longer. 10,25,26 Clari et al 27 reported very lowquality evidence of no statistically significant difference in occlusion rates between short and long flush interval. However, they did not conclude whether flush interval could be extended to a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, some studies have suggested that prolonging the flush interval adequately does not increase the risk of complications after completing chemotherapy. [9][10][11][12][13][14] There is no agreement on the optimal flush interval for patients when ports are not in use. 8 Hence, the purpose of this review was to evaluate whether the flush interval could be prolonged and to identify the optimal maintenance interval.…”
Section: Introductionmentioning
confidence: 99%
“…Although vigorous scientific evidence is lacking, flushing and locking under positive pressure is universally practiced. A proper flush‐lock technique may explain why normal saline can be equally efficacious compared with heparin saline for locking ports , and why the routine monthly flush‐lock as suggested by the manufacturer can be challenged .…”
mentioning
confidence: 99%
“…Besides chemotherapy treatment, Port-a-Caths are frequently used for the administration of medications, blood derivatives, parenteral nutrition and specimen collection for laboratory analysis. [1,2,4,5] Regarding the maintenance of the device, the use of heparin or saline solution prevails over other methods of permeability preservation. However, Number of punction Spearma`s rho= 0.72, p < 0.001 maintenance guidelines are followed according to the directions provided by manufacturers, and literature data concerning the type and amount of solution to be employed as well as maintenance intervals are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, they require less manipulation, a lower frequency in use of heparin flush and reduce the need of dressing, thus contributing to facilitate daily activities and providing individuals with a better quality of life. [2,3,5] Nevertheless, totally implanted CVCs demand constant maintenance so that obstructions and the inadequate performance of the device can be prevented, avoiding risky removals and replacements. Along with the many maintenance techniques for the Port-a-Cath, issues varying from thrombocytopenia induced by heparin to catheter-related bloodstream infections may come up.…”
Section: Introductionmentioning
confidence: 99%